2009
DOI: 10.1002/stem.42
|View full text |Cite
|
Sign up to set email alerts
|

The Actin Polymerization Regulator WAVE2 Is Required for Early Bone Marrow Repopulation by Hematopoietic Stem Cells

Abstract: The Rho GTPase family members play essential roles in hematopoiesis. Of these, Rac1 is thought to be required for the appropriate spatial localization of hematopoietic stem and/or progenitor cells (HSPCs) within the bone marrow (BM), whereas Rac2 likely plays a role in BM retention of HSPCs. To elucidate the molecular mechanisms underlying Rac-mediated functions in hematopoietic stem cells (HSCs), we studied Wiskott-Aldrich syndrome protein family verprolin-homologous proteins (WAVEs), the specific effectors d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Transplantation of HSC populations has been shown to be sufficient for long term multilineage reconstitution, not only in experimental animal models but also in clinical patients with hematological malignancies. HSCs must undergo several steps to achieve engraftment after transplantation, including transendothelial migration into the BM (homing), settling in the BM niche (lodging and retention), and intra-BM proliferation and multilineage differentiation (repopulation) (30). The present study showed that HSCs lacking vinculin were unable to reconstitute the hematopoietic sys- tem efficiently and failed to maintain their self-renewal capacity on BM stromal cell layers.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Transplantation of HSC populations has been shown to be sufficient for long term multilineage reconstitution, not only in experimental animal models but also in clinical patients with hematological malignancies. HSCs must undergo several steps to achieve engraftment after transplantation, including transendothelial migration into the BM (homing), settling in the BM niche (lodging and retention), and intra-BM proliferation and multilineage differentiation (repopulation) (30). The present study showed that HSCs lacking vinculin were unable to reconstitute the hematopoietic sys- tem efficiently and failed to maintain their self-renewal capacity on BM stromal cell layers.…”
Section: Discussionmentioning
confidence: 64%
“…Cobblestone-like Area Forming Assay-Cobblestone-like area forming assays were essentially performed as reported previously (30). C3H/10T1/2 cells were cultured in 96-well plates and then irradiated with a single dose of 50 grays.…”
Section: Isolation Of C-kitmentioning
confidence: 99%
“…First, adherent CD34 ϩ cells ( Figure 2D) exhibited dense areas of polymerized filamentous actin (F-actin) in the cortical cytosol, demonstrating the activated status of the cells, which is secondary to PI3K-dependent activation involving Rac1, protein kinase C-, extracellular signal-regulated kinase 1/2, and WAVE2. 11 In contrast, nonsheared CD34 ϩ cells show diffuse low-level staining of F-actin ( Figure 2C).…”
Section: Homed Cd34mentioning
confidence: 94%
“…Interestingly, FN is a major component of bone marrow ECM and may modulate homing of hemopoietic progenitor cells 41 and the organization and composition of bone marrow ECMs and cell-matrix adhesion sites. 40 The present work suggests a new role for MKs as promoters of matrix deposition and remodeling within the bone marrow environment, with particular emphasis on the type I collagen-rich osteoblastic niche.…”
Section: Discussionmentioning
confidence: 99%